Machine infelicity in a poignant visitor setting: comparing human and AI's ability to analyze discourse. Issue 8 (18th April 2022) - MacCarthy, Martin; Shan, Hairong
ABSTRACT: This study compares the efficacy of computer and human analytics in a commemorative setting. Both deductive and inductive reasoning are compared using the same data across both methods. The data comprises 2490 non-repeated, non-dialogical social media comments from the popular touristic site Tripadvisor. Included in the analysis is participant observation at two Anzac commemorative sites, one in Western Australia and one in Northern France. The data is then processed using both Leximancer V4.51 and Dialectic Thematic Analysis. The findings demonstrate artificial intelligence (AI) was incapable of insight beyond metric-driven content analysis. While fully deduced by human analysis the metamodel was only partially deduced by AI. There was also a difference in the ability to induce themes with AI producing anodyne, axiomatic concepts. Contrastingly, human analytics was capable of transcendent themes representing ampliative, phronetic knowledge. The implications of the study suggest (1) tempering the belief that the current iteration of AI can do more than organise, summarise, and visualise data; (2) advocating for the inclusion of preconception and context in thematic analysis, and (3) encouraging a discussion of the appropriateness of using AI in research.